Differences in the performance tests of the fast and slow stretch and shortening cycle among professional, amateur and elite youth soccer players - Keiner, M.; Sander, A.; Wirth, K.; Hartmann, H. (Journal of Human Sport & Exercise, 2015)
The purpose of this study was to establish whether physical attributes can differentiate between professional, amateur and elite youth soccer players; such a distinction could aid in the selection process for youth soccer. Therefore, this investigation evaluated a suspected difference in the performance tests of the slow and fast stretch and the shortening cycle (squat jump [SJ], counter-movement jump [CMJ], and drop jump from varying heights [DJ]) among professional, amateur and elite youth soccer players. Cross-sectional data were collected. The results indicate that higher performance in the SJ and CMJ seem to depend on the level of player because the mean performance of the PRO was 38.7 ± 4.0 cm in the SJ and 41.2 ± 3.8 in the CMJ, which were significantly (p<0.05) different compared with all other groups. In the DJ, there were significant (p<0.05) differences between the professional players (PRO) and lower-level players as well as between the PRO and youth soccer players. The results suggest that jump performance can differentiate between elite, sub-elite, and youth soccer players and highlights the importance of appropriate conditioning for developing strength and power in youth soccer players.